Cultural Understanding In English Language Learning - Wuri Syaputri; Fenny Theresia; Fatma Yuniarti (SIGEH ELT : Journal of Literature and Linguistics, 2021)
Language and culture are two things that are interrelated in human life, especially in learning and langage teaching. The objective of this study is to dercribe the understanding of culture in learning English. This research belongs to qualitative research which applies libraries research to collect the data. The introduction of this culture is especially recommended for foreign language learning which places more emphasis on developing communication skills with the target language. The introduction of culture in learning English process can reduce the potential for misunderstandings to occur during the communication process.